Sphingosine-kinase-1 signaling promotes metastasis of triple-negative breast cancer - Acharya, Sunil (Cancer Res, 2019)
Triple negative breast cancer (TNBC) is the most aggressive breast cancer subtype. To identify TNBC therapeutic targets, we performed integrative bioinformatics analysis of multiple breast cancer patient-derived gene expression datasets and focused on kinases with FDA-approved or in-pipeline inhibitors. Sphingosine kinase 1 (SPHK1) was identified as a top candidate. SPHK1 overexpression or downregulation in human TNBC cell lines increased or decreased spontaneous metastasis to lungs in nude mice, respectively. SPHK1 promoted metastasis by transcriptionally upregulating the expression of the metastasis-promoting gene FSCN1 via NFκB activation. Activation of the SPHK1/NFκB/FSCN1 signaling pathway was associated with distance metastasis and poor clinical outcome in TNBC patients. Targeting SPHK1 and NFκB using clinically-applicable inhibitors (safingol and bortezomib, respectively) significantly inhibited aggressive mammary tumor growth and spontaneous lung metastasis in orthotopic syngeneic TNBC mouse models. These findings highlight SPHK1 and its downstream target NFκB as promising therapeutic targets in TNBC.